Research on Non-inertial System Effect of Dynamic Stress of Planetary Gear System under Basic Motion - Aiqiang Zhang; Guangbin Yu; Miaofei Cao; Jing Wei (Jixie chuandong)
Considering the comprehensive influence of the internal non-inertial system of the planetary gear system and the external non-inertial system of the body's time-varying attitude，a dynamics model of the planetary gear transmission system under the non-inertial system is established. Combining the modified Heywood formula and Hertz formula，a calculation model of the tooth root bending dynamic stress and contact dynamic stress of the planetary gear transmission system under the basic motion non-inertial system is constructed，and the stress non-inertial system coefficients describing the influence of the additional effects on the dynamic stress under the basic motion are defined. The variation law of the stress non-inertial system coefficients under three typical maneuvering conditions such as variable speed level flight，roll motion and somersault motion is studied. The results show that the stress non-inertial system coefficients are closely related to the basic motion form and motion parameters. Generally，the stress non-inertial system coefficients increase in a non-linear increase in the mobility of random bodies，and the influence of the basic motion cannot be ignored under high maneuvering conditions.